Effect of Pattern Shape on the Initial Deposition of Particles in the Aqueous Phase on Patterned Membranes during Crossflow Filtration - Choi, Dong-Chan (2017)
Patterned membranes for water treatment processes have been proposed to mitigate the detrimental effect of membrane fouling. Analysis of the effects of various pattern shapes on antifouling properties is required to achieve a higher resistance to fouling in these membranes. In this study, membranes for water treatment with unpatterned, pyramid, reverse-pyramid, and 45°-rotated pyramid patterns were prepared, and their antifouling effects were compared by measuring the extent of particle deposition during crossflow filtration. The 45°-rotated pyramid patterns were the most effective in reducing particle deposition. Computational fluid dynamics modeling was conducted for each membrane surface to elucidate the differences between the antifouling properties of various patterns in terms of shear stress and flow regime.